(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Academic achievement is a central indicator of students’ educational progress and overall development. Understanding the level of academic achievement among secondary school students is essential for evaluating the effectiveness of teaching–learning processes and identifying areas for improvement. The present study aimed to examine the level of academic achievement among secondary school students. A descriptive survey method was employed on a sample of 800 Class IX students drawn from government and private schools of Bilaspur district, Chhattisgarh, India. Academic achievement was measured using students’ official examination scores obtained from school records. Descriptive statistical techniques such as mean, standard deviation, frequency, and percentage were used for analysis. The findings revealed that the majority of students demonstrated moderate to high levels of academic achievement, with most students falling in the Average, Above Average, and High categories, while only a small proportion exhibited low achievement levels. The results indicate generally satisfactory scholastic performance among students but highlight the need for targeted interventions to support lower-performing learners. The study provides useful insights for educators, policymakers, and researchers aiming to improve academic outcomes in secondary education.